2009
DOI: 10.1007/s00701-009-0382-6
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant Acinetobacter baumannii ventriculitis: successful treatment with intraventricular colistin

Abstract: Acinetobacter baumannii has emerged as an important nosocomial pathogen that can cause a multitude of severe infections. In neurosurgical patients the usual presentation is ventriculitis associated with external ventricular drainage. Carbapenems have been considered the gold standard for the treatment of Acinetobacter baumannii ventriculitis, but resistant isolates are increasing worldwide, reducing the therapeutic options. In many cases polymyxins are the only possible alternative, but their poor blood-brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 25 publications
0
19
0
1
Order By: Relevance
“…baumannii, which is a gram-negative, non-fermentative coccobacillus of the family Moraxellaceae, is considered to be an important cause of ventilator-associated pneumonia, sepsis, urinary system infection and meningitis (11)(12)(13)(14)(15)(16)(17) (18). We speculated that this descrepency may be due to the strains selected in this study.…”
Section: Discussionmentioning
confidence: 87%
“…baumannii, which is a gram-negative, non-fermentative coccobacillus of the family Moraxellaceae, is considered to be an important cause of ventilator-associated pneumonia, sepsis, urinary system infection and meningitis (11)(12)(13)(14)(15)(16)(17) (18). We speculated that this descrepency may be due to the strains selected in this study.…”
Section: Discussionmentioning
confidence: 87%
“…Colistin has also been used recently to treat ventilator-associated pneumonia (VAP) and bacteremia caused by MDR bacteria, such as P. aeruginosa, K. pneumoniae and A. baumannii [ [133] and Dalgic et al [134] suggested that intraventricular administration of CMS is effective for the treatment of ventriculitis caused by MDR A. baumannii.…”
Section: Reviewmentioning
confidence: 99%
“…First, for those clinicians referring to published reports of studies involving CMS/colistin to guide their practice, insufficient detail is often provided in published papers to ascertain the doses of CMS actually used. Confusion regarding this is illustrated in a recent review [19] of intraventricular CMS for treatment of A. baumannii ventriculitis, where doses of CMS were tabulated in mg but for a product labeled with ‘colistin base activity’ [20] it was not clear whether the mg of ‘colistin base activity’ had been converted to mg of CMS). The second unresolved issue is the most appropriate daily dose.…”
Section: Do We Know How To Optimize Dosing Of Colistin?mentioning
confidence: 99%
“…The intrathecal or intraventricular administration of CMS to treat CNS infections has been reviewed previously [6, 8, 57] and reports continue to accumulate [19, 58]. Administration via these routes is usually instituted when there is concern that intravenous CMS will adequately penetrate into site of infection or when intravenous administration has actually been shown to be ineffective.…”
Section: Current Clinical Uses Of Colistinmentioning
confidence: 99%
See 1 more Smart Citation